PENGEMBANGAN E-BOOKLET RAGAM KOLONI JAMUR MIKROSKOPIS PADA RHIZOSFER TANAMAN Capsicum frutescens dan Solanum melongena L. DI KELURAHAN LANDASAN ULIN UTARA - Damayanti, Arma; Ajizah, Aulia; Noorhidayati, Noorhidayati (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
The rhizosphere of plants contains diverse microbial communities, including fungi. This study aimed to identify the diversity of fungal colonies in the rhizosphere of plants and to describe the validation results, readability, and student responses toward the developed e-booklet as a learning medium. The e-booklet entitled “Diversity of Microbial (Fungal) Colonies in the Rhizosphere of Capsicum frutescens and Solanum melongena L.” was developed based on research conducted in North Landasan Ulin. The fungal colonies obtained were identified according to their morphological characteristics based on literature, and the findings were further developed into digital learning materials using the ADDIE development model. The validation test was conducted by three expert validators, while the readability and response tests were carried out by twelve students who had completed the Microbiology course in the Biology Education Study Program, Faculty of Teacher Training and Education, Lambung Mangkurat University, Banjarmasin. The results revealed three microscopic fungal colonies in the Capsicum frutescens rhizosphere soil samples and seven colonies in the Solanum melongena L. samples. The material validation test obtained a score of 98.75% (very valid), and the media validation test obtained a score of 78.66% (valid), indicating that the developed e-booklet is suitable for instructional use. The readability test achieved a score of 89.46% (excellent), and the student response test achieved 90.17% (excellent), demonstrating that the e-booklet is effective and easy for students to understand.